Environmental heavy metal as a potential risk factor for the progression of oral potentially malignant disorders in central Taiwan. (April 2017) - Tsai, Kuo-Yang; Su, Che-Chun; Chiang, Chi-Ting; Tseng, Yao-Ting; Lian, Ie-Bin
Highlights: The first study to associate environmental metal and oral cancer (OC) among oral potentially malignant disorders (OPMD) patients. After adjustment, OPMD patients in high nickel areas had nearly 2-fold hazard for OC to those in low nickel areas. OPMD patients in high nickel areas should be more cautious on developing OC, and intense monitoring programs may be needed. Abstract: Objective: Oral cancer (OC) is a leading cause of death from cancer in men between the ages of 25 and 44 years in Taiwan. The overall 5-year survival rates for the four OC stages (I–IV) in Taiwan are approximately 70%, 30%, 20%, and 10%, respectively, indicating the importance of the early diagnosis of oral potentially malignant disorders (OPMDs). Previous studies indicated an association between the OC incidence and certain environmental heavy metal concentrations. If these associations do exist for OC, they may also be observed for OPMD. The purpose of this study is to explore the association between the development of OPMD to OC and environmental heavy metals. Oral submucous fibrosis (OSF) and oral leukoplakia (OL) are two major types of OPMD in Taiwan. Materials and methods: A retrospective cohort study was conducted by Changhua Christian Hospital, the sole medical center in Changhua County, where 2725 male adult patients diagnosed with either OSF or OL between 2000 and 2014 were recruited. Data were analyzed by Cox regression and adjusted for smoking and betel-quid chewing. Results and discussion: OPMD patients who resided in areas with high nickel concentrations (polluted levels) exhibited hazard ratios of 1.8–2 for OC relative to those who lived in areas with low nickel levels ( P <  0.01). Meanwhile, smokers with OPMDs had a hazard ratio of 2.8–2.9 relative to non-smokers. Betel-quid chewers had a 2.2–2.3 hazard ratio relative to non-chewers. Smoking, betel-quid chewing, and environmental nickel exposure are associated with an increased risk of OC development in OPMD patients. This study provides valuable findings on the environmental effects of heavy metals on human health. Enhanced surveillance of the condition of OPMD patients who have been exposed to high nickel concentrations may be crucial for OC prevention.